Carbonate‐Based Fluorescent Chemical Tool for Uncovering Carboxylesterase 1 (CES1) Activity Variations in Live Cells. (21st March 2022) - Singh, Anchal; Gao, Mingze; Karns, Carolyn J.; Spidle, Taylor P.; Beck, Michael W.
Abstract: Carboxylesterase 1 (CES1) plays a key role in the metabolism of endogenous biomolecules and xenobiotics including a variety of pharmaceuticals. Despite the established importance of CES1 in drug metabolism, methods to study factors that can vary CES1 activity are limited with only a few suitable for use in live cells. Herein, we report the development of FCP1, a new CES1 specific fluorescent probe with a unique carbonate substrate constructed from commercially available reagents. We show that FCP‐1 can specifically report on endogenous CES1 activity with a robust fluorescence response in live HepG2 cells through studies with inhibitors and genetic knockdowns. Subsequently, we deployed FCP‐1 to develop a live cell fluorescence microscopy‐based approach to identify activity differences between CES1 isoforms. To the best of our knowledge, this is the first application of a fluorescent probe to measure the activity of CES1 sequence variants in live cells. Abstract : Despite the established importance of carboxylesterase 1 (CES1) in drug metabolism, methods to monitor factors that influence CES1 activity are limited. Herein, we exploit the self‐immolative properties of carbonates to generate a fluorescent chemical tool and use it to identify activity differences between CES1 sequence variants in live cells.